Teaching-learning strategies on patient safety in higher education institutions: a scoping review - Nicole Ferreira Netto; Vanessa Albuquerque Alvim de Paula; Marcelo Carneiro; Vilanice Alves de Araújo Püschel; Fábio da Costa Carbogim; André Luiz Silva Alvim (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to map the scientific production on teaching-learning strategies related to patient safety in higher education institutions across Nursing, Pharmacy, Medicine, and Dentistry programs. Methods: this scoping review follows the Joanna Briggs Institute (JBI) guidelines and the PRISMA Extension for Scoping Reviews recommendations. The selection of studies was performed using databases, grey literature, and reverse searching, conducted by two independent and blinded reviewers. Results: nineteen studies were included, the majority of which were conducted at the undergraduate level, primarily among nursing students. The identified teaching-learning strategies included clinical simulation, courses, competency assessment, and expository methods. Additional strategies employed were workshops, structured objective clinical examinations, flipped classrooms, team testing, questionnaire applications, dramatization, and games. Conclusions: the most commonly used teaching-learning strategies were clinical simulation and courses on patient safety.